High-frame rate and high-count rate hybrid pixel detector for 4D STEM applications - Zambon, P.; Vávra, J.; Montemurro, G.; Bottinelli, S.; Dudina, A.; Schnyder, R.; Hörmann, C.; Meffert, M.; Schulze-Briese, C.; Stroppa, D.; Lehmann, N.; Piazza, L. (Frontiers in Physics, 2023)
We present the performance assessment of a novel hybrid pixel detector. The electron counting ASIC, called KITE, was optimized for 4D STEM applications, and bump-bonded to a silicon sensor it is suitable for electron energies in the range 30–200 keV. The KITE ASIC was developed for high frame rate, currently up to 120 kfps, and high count rate, thanks to fast signal shaping times and the instant retrigger technology, which allows operating in a characteristic non-paralyzable counting mode. Investigated quantities include the spectral response, the identification of optimal threshold energies, an estimation of the threshold trimming accuracy, the analysis of the single event multiplicity distributions, the count rate capabilities, imaging performance metrics MTF and DQE. To highlight the capabilities of the detector, best value of 10% of linearity loss was achieved at 84 Mcts/s/pix, best value of count rate “cutoff” at nearly 150 Mcts/s/pix and DQE(0) between 0.75 and 0.82 up to the electron energy of 160 keV.